2022
DOI: 10.3390/catal12030246
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Eggshells as Natural Heterogeneous Catalysts for Transesterification of Rapeseed Oil with Methanol

Abstract: Heterogeneous catalysis has an advantage of easy separation of the catalyst after biodiesel is produced. CaO is known to be an efficient heterogeneous catalyst for biodiesel production. Taking into account that CaO is a key component of eggshells, the effectiveness of eggshells as a heterogeneous catalyst for rapeseed oil transesterification with methanol was investigated and optimal conditions of biodiesel production were determined applying RSM methodology. The influence of three independent variables on est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…The researchers studied the process of methanolysis of rapeseed oil by changing the amount of eggshell from 4 to 10 wt%. The optimal amount was determined to be 6.8 wt% [21]. Wei et al obtained a very similar optimal amount of catalyst as in this study, although methanol was used in the process [22].…”
Section: Modeling and Determination Of Optimal Reaction Conditionsmentioning
confidence: 65%
See 2 more Smart Citations
“…The researchers studied the process of methanolysis of rapeseed oil by changing the amount of eggshell from 4 to 10 wt%. The optimal amount was determined to be 6.8 wt% [21]. Wei et al obtained a very similar optimal amount of catalyst as in this study, although methanol was used in the process [22].…”
Section: Modeling and Determination Of Optimal Reaction Conditionsmentioning
confidence: 65%
“…A study on the synthesis of soyabean oil methyl ester was conducted by Wei et al [22]; it was found that the optimal alcohol-to-oil molar ratio is 9:1, and the same optimal molar ratio of methanol-to-oil was determined by Graziottin et al [28]. Gaide et al [21] determined that an increase in the yield of rapeseed oil methyl ester is observed until the methanol-to-oil molar ratio increases up to 13:1, and further increase in the methanol amount leads to a decrease in the ester yield. Therefore, a high amount of alcohol is not desirable for the transesterification process as it can increase reversible reaction [35].…”
Section: Modeling and Determination Of Optimal Reaction Conditionsmentioning
confidence: 90%
See 1 more Smart Citation
“…The most commonly used acyl acceptors in biodiesel synthesis are alcohols. Most studies on biodiesel production have been conducted using methanol [ 18 , 24 , 25 ], ethanol [ 19 , 26 ], and butanol [ 7 , 21 ]. Some researchers are conducting transesterification studies with longer and branched chain alcohols [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using heterogeneous catalysts has the benefit that they can be easily separated from the final products and reused. Waste products, including eggshells, mollusk shells, fishbone, golden, and mud crab shells, are inexpensive and can be used as heterogeneous catalysts for biodiesel synthesis [18,19].…”
Section: Introductionmentioning
confidence: 99%